From occasion to obsession: the connection between relationships, media literacy and the changing use of computer mediated communication from 2005-2018 - Dempsey, Lauren (2021)
2005-2018 saw an era of rapid technological change, particularly with regards to digital media and computer mediated communication (CMC). During this time mobile phone ownership grew, the internet became a key utility in UK homes, and the development of various online platforms – such as email, video calling and social media – led to CMC use becoming increasingly normalised. Academics and regulators queried how best to promote media literacy skills in this ever-changing media landscape, where rapidly changing forms of CMC meant it was increasingly difficult to determine how and why literacy skills were developed.